In Sight : My Life in Science and Health Innovation. - Levy, Julia (University of Toronto Press, 2020)
Covering issues within the scientific community, In Sight is a deeply personal memoir of a woman's experience transitioning a major scientific treatment from grassroots development to commercial breakthrough.